Rancang Bangun 3 Dimensi Hologram Sebagai Media Informasi Mengenal Hewan Mamalia - Dyandra Hutama Abdi; Rismayanti Rismayanti; Putri Harliana (UIN Sumatera Utara, 2022)
The development of digital technology today has grown rapidly in everyday life. Advances in technology can now be accessed easily so that users of computer technology encourage people to be creative and innovate. However, the development of the past few years, the world of visual communication design has begun to develop towards an alternative 3d virtual reality technology called